Green Banking and Green Central Banking - Berrigan, John; Boivin, Jean; Bräunig, Günther; Campa, Jose Manuel; Dombret, Andreas; Draijer, Wiebe; Fishwick, Ed; Goulard, Sylvie; Hildebrand, Philipp; Hoyer, Werner; Issing, Otmar; Kenadjian, Patrick S.; et al. (Institute for law and finance series, 2022)
The books deals with the questions that really matter for green finance: Where will the money to finance the transition to a low carbon environment come from, how far do the banks' balance sheets stretch and where will the rest of the money come from? How much can we rely on the capital markets, especially in the EU, to get money to the parts of the economy which really need it, without greenwashing? How do governments organize not just a transition, but a just transition to a low carbon environment? Is it time to revisit received ideas about the proper role for centralbanks?